The Frictional Coefficient Comparison Between Stainless Steel And Beta- Titanium Arch wires Ligatured to the Stainless Steel Bracket Via Different Ligatures - Hussain A Obaidi; Anas M Al-Mukhtar (University of Mosul, College of Dentistry, 2008)
Aims: To compare the frictional coefficients between the stainless steel and B-titanium arch wire liga-tured to the stainless steel bracket via different ligatures. Materials and Methods: The sample of the study included the stainless steel and β-Titanium arch wire groups, the wire group comprised of three subgroups, each wire subgroup ligatured to stainless steel brackets via different ligatures. The mea-surement of the frictional coefficient was performed using the simulated side arch fixed appliance at-tached to the tensile machine. The data were analyzed by using the descriptive and variance statistical tests at p≤ 0.05 significance level. Results: The results demonstrated that the stainless steel arch wire tied to the bracket via stainless steel ligature achieved significant lower frictional coefficient value when compared with other wire subgroups. Conclusions: The combination of the stainless steel; arch wire, bracket and ligature is more practical choice in sliding orthodontic treatments.